2003
DOI: 10.2533/000942903777678669
|View full text |Cite
|
Sign up to set email alerts
|

The Crocacins: Novel Natural Products as Leads for Agricultural Fungicides

Abstract: Septoria nodorum (wheat glume blotch). We also confirmed their mode of action as inhibition of mitochondrial respiration at complex III in beef heart and the model fungus Neurospora crassa.With their novel structures, interesting mode of action and significant fungicidal activity, the crocacins were attractive leads for synthesis, although ambitious targets as agrochemicals due to their relatively complex structures. We therefore decided to embark on a programme of chemistry to see if simpler, more active and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…In our first analogues, we replaced the whole the side chain with simple n-alkyl chains 27,28. We were gratified to find that certain analogues, for example, 12 (Table 4), were very active in the beef heart mitochondrial respiration assay but unfortunately showed no fungicidal activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our first analogues, we replaced the whole the side chain with simple n-alkyl chains 27,28. We were gratified to find that certain analogues, for example, 12 (Table 4), were very active in the beef heart mitochondrial respiration assay but unfortunately showed no fungicidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, 24 was only very weakly active on the NADH oxidase assay (see Table 5). Another approach that had been employed with the β-methoxyacrylates, was incorporation of the cis -double bond into a benzene ring,27 as in 25 , but this type of analogue was completely inactive. This was consistent with our model, which shows that there is no space for an additional ring.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, at Syngenta several simplified analogues were prepared to overcome these potential limitations (Crowley et al 2003). It was demonstrated that the complex side chain could be simplified significantly by replacing the side chain with bisarylethers as in 33, or by benzylaryl groups as in 34, whilst maintaining biological activity in vitro and in vivo (Fig.…”
Section: Synthetic Analogues Of Herbicidal Leptospermonementioning
confidence: 99%
“…Crocacin B (30) and crocacin C (31) did not exhibit significant biological activity (Crowley et al 2003).…”
Section: Synthetic Analogues Of Herbicidal Leptospermonementioning
confidence: 99%
“…O modo de ação apresentado pelas crocacinas A (1) e D (4) sobre o crescimento de fungos despertou o interesse de Crowley e colaboradores 18 em sintetizar análogos nos quais a alta complexidade da cadeia lateral foi substituída por subunidades aromáticas mais simples e contendo funcionalidades que pudessem mimetizar as encontradas nas estruturas das crocacinas. Apesar dos análogos apresentarem maior estabilidade fotoquímica que os produtos naturais, eles continuaram a ter tempos de meia-vida relativamente curtos na superfície das plantas, o que provavelmente se deve à instabilidade fotoquímica da função (Z)-enamida e infelizmente nenhum dos compostos foi ativo o suficiente para estudos posteriores.…”
unclassified